Uncertainty and challenges in contemporary economic behaviour - Özen, Ercan; Grima, Simon (Emerald Studies in Finance, Insurance, and Risk Management, 2020)
Every day presents new challenges as the face of global economics changes. In this first book in the Emerald Studies in Finance, Insurance, and Risk Management, expert editors and contributors come together to discuss global response to new uncertainty and challenges.- Resumé vydavatel